PENGARUH KECERDASAN EMOSI DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA DI SMP NEGERI 1 SENGKANG - Yulika, Rian (Inspiratif Pendidikan, 2019)
Abstract:This study aims to determine the effect of emotional intelligence and learning motivation on student achievement in Junior High School 1 Sengkang. Quantitative research approach with the type of Ex Post Facto research. The population in this study were 297 students, the research sample was 149 students. The method used in data collection is the scale of psychology and documentation. Data analysis techniques used descriptive statistical analysis techniques and inferential statistical analysis. The results showed that the influence of emotional intelligence variables and learning motivation together on learning achievement was 3.5% with a significance value of p = 0.028 ≤α (0.05). This shows that there is a significant positive influence between emotional intelligence and learning motivation on student achievement in Junior High School 1 Sengkang. AbstractThis study aims to determine the effect of emotional intelligence and learning motivation on student achievement in Junior High School 1 Sengkang. Quantitative research approach with the type of Ex Post Facto research. The population in this study were 297 students, the research sample was 149 students. The method used in data collection is the scale of psychology and documentation. Data analysis techniques used descriptive statistical analysis techniques and inferential statistical analysis. The results showed that the influence of emotional intelligence variables and learning motivation together on learning achievement was 3.5% with a significance value of p = 0.028 ≤α (0.05). This shows that there is a significant positive influence between emotional intelligence and learning motivation on student achievement in Junior High School 1 Sengkang.